Health sciences librarians' attitudes toward the Academy of Health Information Professionals - Baker, Lynda M. (Medical Library Association, 2004)
Objectives: The purpose of the study was to ascertain health sciences librarians' attitudes toward the Academy of Health Information Professionals (AHIP). Sample: Systematic sampling was used to select 210 names from the list of members of the Midwest Chapter of the Medical Library Association. Methods: A questionnaire containing open- and closed-ended questions was used to collect the data. Results: A total of 135 usable questionnaires were returned. Of the respondents, 34.8% are members of the academy and most are at the senior or distinguished member levels. The academy gives them a sense of professionalism and helps them to keep current with new trends. The majority of participants (65.2%) are not members of the academy. Among the various reasons proffered are that neither institutions nor employers require it and that there is no obvious benefit to belonging to the academy. Conclusions: More research needs to be done with a larger sample size to determine the attitudes of health sciences librarians, nationwide, toward the academy.